Comparison of reading comprehension in students of 4th to 6th grade of elementary school from public and private schools of Lima metropolitana - Delgado Vásquez, Ana Esther (2005)
OBJECTIVES: a. To study reading comprehension development on students of fourth to sixth grade of primary school. b. To analize the comprehension developmental change of public and private schools students of fourth, fifth, and sith grade of primary school. c. To compare the developmental level of reading comprehension of fourth to sixth grade considering biological sex. d. To set the instruments psychometrics properties. e. To study the reading comprehension model using the confirmatory factor analysis. DESIGN: Descriptive comparative study, carried on public and private primary school students from fourth to sixth grade. MATERIALS AND METHODS: A byetapic conglomerate sampling affixed to size, the participantes were 780 students of each three grades belonging to seven units (UGEL) of the city of Lima, Peru. The instruments were the spanish version of a reading comprehension test, named «Prueba de Comprensión Lectora de Complejidad Lingüística Progresiva» for fourth to sixth grade respectively. The statistical analysis considered three stages: Psycometric study in order to calculate validity and reliability index, descriptive analysis, and inferential hypothesis testing. RESULTS: It has been found that all the instruments have appropiate validity and reliability values. There were not significative differences on reading comprehension among students from public and private schools of fourth grade of primary school, either are not differences considering the biological sex of the students. There were significative differences on reading comprehension among students from public and private schools of fifth grade of primary school. It was found significative differences on reading comprehension only on students from public schools, considering the biological sex, showing males higher scores than females. There were significative differences on reading comprehension among the students from public and private schools of sixth grade, also it was find statistically significative differences considering biological sex, showing the female students higher scores than the male students.